Micropropagation and ex situ conservation of Silene fabaria (L.) Sm. in Sibth. & Sm. subsp. domokina Greuter (Caryophyllaceae); an important endemic plant in Greece with medicinal and ornamental value - Sarropoulou, Virginia; Maloupa, Eleni (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2019)
Silene species (Caryophyllaceae) are sources of important secondary metabolites with extensive use in traditional medicine and potential applications as ornamentals. The present study was conducted to assess the regeneration potential of Silene fabaria subsp. domokina to produce massive clonal in vitro plants. Two experiments were conducted. The basal culture medium used was the MS. In the first experiment, the effect of 3 cytokinins; BA, KIN and 2-ip applied alone and in combination with 3 auxins; IBA, NAA and IAA was studied. In the second experiment, the effect of 3 auxins; IBA, NAA and IAA, each applied in 3 different concentrations (0.1, 0.25 and 0.5 mg/l) was studied. Shoot proliferation 100%, highest shoot proliferation rate (4.83) and shoot number (3.67) were achieved with 0.25 mg/l BA and 0.1 mg/l IAA (5 weeks). IAA at 0.5 mg/l was the most effective in stimulating shoot elongation (80.63 mm). Rooting 100% was obtained with 0.1 mg/l IBA yielding 7.3 roots 22.91 mm long (4 weeks). In vitro plants were successfully acclimatized with 92.31% survival rate. This study is the first micropropagation report of S. fabaria subsp. domokina that could be exploited for rapid, large-scale production and future germplasm maintenance of this valuable prioritized species-subspecies.